Given the set of equations:
y - 3x = 5
2x - y = -2
Let's graph the set of equations.
Rewrite the equations in slope intercept form:
y = mx + b
Where m is the slope and b is the y-intercept
Let's rewrite both equations for y.
Equation 1:
y - 3x = 5
Add 3x to both sides of the equation:
y - 3x + 3x = 3x + 5
y = 3x + 5
Equation 2:
2x - y = -2
Subtract 2x from both sides:
2x - 2x - y = -2x - 2
-y = -2x - 2
Divide all terms by -1:
![\begin{gathered} (-y)/(-1)=(-2x)/(-1)+(-2)/(-1) \\ \\ y=2x+2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7oaoks6pb0clbblsb28o94ego7wyaeksxf.png)
Thus, we have both equations in slope intercept form:
y = 3x + 5
y = 2x + 2
To graph, let's mark two points each from each equation.
y = 3x + 5
When x = 1
y = 3(1) + 5 = 3 + 5 = 8
When x = -1
y = 3(-1) + 5 = -3 + 5 = 2
Mark the points on the graph and connect using a straight line:
(x, y) ==> (1, 8) and (-1, 2)
• y = 2x + 2
When x = 1
y = 2(1) + 2 = 2 + 2 = 4
When x = -1
y = 2(-1) + 2 = -2 + 2 = 0
Mark the points on the graph and connect using a straight line:
(x, y) ==> (1, 4) and (-1, 0)
Thus, we have the graph below:
From the graph, we can see the point where both lines meet is at (-3, -4).
This means the solution to the set of equations is: (-3, -4)